Health risk assessment of Patulin intake through apples and apple-based foods sold in Qatar - Iman Saleh (14152878) (2019)
This is the first report on assessing the non-carcinogenic health risk associated with Patulin exposure in Qatar. The concentrations of Patulin, as determined in previous studies, in apples, apple juice, and apple-based baby foods sold in Qatar and nearby countries were used to conduct the health risk assessment (HRA). The risk related to Patulin intake by different age groups was calculated using the USEPA risk assessment models. The intake levels (ILs) of various age groups was compared with the international standards. The highest IL in Qatar was for babies between 5-12 months old through ingesting contaminated apple-based baby foods, yet those levels were below the tolerable daily intake of Patulin set by the EU at 0.4 μg/kg BW/d. The results showed that the intake of Patulin in Qatar is lower than that in Tunisia and Iran based on the HRA analysis. The risk caused by chronic exposure to Patulin through ingesting raw apples and apple juice separately was below “1,” indicating that the overall population is not likely to be at risk of Patulin exposure. However, various uncertainties should be considered when adopting these results, mainly the low number of samples and additive exposure to other mycotoxins from different sources. Other Information Published in: Heliyon License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.heliyon.2019.e02754